2020
DOI: 10.1186/s12920-020-00845-3
|View full text |Cite
|
Sign up to set email alerts
|

The C allele of the reactive oxygen species modulator 1 (ROMO1) polymorphism rs6060566 is a biomarker predicting coronary artery stenosis in Slovenian subjects with type 2 diabetes mellitus

Abstract: Background We aimed to examine the role of the rs6060566 polymorphism of the reactive oxygen species modulator 1 (ROMO1) gene in the development of myocardial infarction (MI) in Caucasians with type 2 diabetes (T2DM). Methods A total of 1072 subjects with T2DM were enrolled in this cross-sectional case–control study: 335 subjects with MI and 737 subjects without clinical signs of coronary artery disease (CAD). The genetic analysis of the rs6060566 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…One of the crucial cytokines involved in the pathogenesis of psoriasis and RA, IL-17, has been reported to play an important role in the production of reactive oxygen species (ROS) [10,20]. ROS are on the list of factors that can cause endothelial dysfunction [6]. IL-17 is one of the main factors for endothelial dysfunction in patients with RA [21].…”
Section: Pathogenesis Of Atherosclerosis In Selected Inflammatory Con...mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the crucial cytokines involved in the pathogenesis of psoriasis and RA, IL-17, has been reported to play an important role in the production of reactive oxygen species (ROS) [10,20]. ROS are on the list of factors that can cause endothelial dysfunction [6]. IL-17 is one of the main factors for endothelial dysfunction in patients with RA [21].…”
Section: Pathogenesis Of Atherosclerosis In Selected Inflammatory Con...mentioning
confidence: 99%
“…Endothelial dysfunction causes changes in the production of endothelial cells (i.e. expression of adhesion molecules, ROMO1 expression and production of inflammatory cytokines…), and they lead to morphological changes in the vessel wall (inflammation, atherosclerotic changes) [1,2,6]. IL-1β, IL-6, IL-17, TNF-α and hs-CRP are involved in the pathogenesis of atherosclerosis, psoriasis and RA [23,24].…”
Section: Pathogenesis Of Atherosclerosis In Selected Inflammatory Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated circulating markers such as C-reactive protein (CRP), interleukins (IL) (IL-1β, IL-6, IL-8, IL-12, IL-17, IL-32, IL-36), tumor necrosis factor α (TNFα), and vascular endothelial growth factor (VEGF) are commonly found in conditions of low-grade inflammation, such as CVD, psoriasis, RA, and diabetes mellitus (DM) [ 4 , 5 , 6 ]. Immune cells of innate or adaptive immunity (monocytes, neutrophils, mast cells, macrophages, and lymphocytes) are thought to play an important role in chronic inflammation [ 6 , 7 ]. Moreover, they were reported to be responsible for the production of inflammatory cytokines [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…As of now, genome-wide association studies have identified more than 50 independent loci associated with cardiovascular diseases that collectively account for 13.3% of their heritability ( Nikpay et al, 2015 ). One study investigated the role of oxidative stress ROM O 1 gene polymorphism and showed that subjects carrying the C allele were at a more than three folds increased risk of developing cardiovascular diseases ( Tibaut et al, 2020 ). Therefore, an in-depth exploration of oxidative stress will help us understand how this disease develops and will also provide new ideas for its prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%